1997
DOI: 10.2516/ogst:1997015
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal Structure of Heavy Crudes and Asphaltene Soltutions

Abstract: STRUCTURE COLLOIDALE DES BRUTS LOURDS ET DES SUSPENSIONS D'ASPHALTÈNESL'industrie pétrolière est souvent confrontée a des problèmes industriels importants liés, entre autre, à la présence d'une forte concentration d'asphaltènes dans les fluides traités. Une meilleure connaisssance de la composition de ces molécules et de l'évolu tion de leur structure colloïdale en solution ou dans leur milieu naturel est d'une grande importance pour mieux comprendre les mécanismes mis en jeu, et ainsi, pouvoir agir et limiter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(80 citation statements)
references
References 9 publications
2
78
0
Order By: Relevance
“…Fairly reliable values of average volume by weight, molar mass by weight and radius of gyration can be deduced from experimental measurements without using distribution models. In contrast, Barré et al (1997) demonstrated that the experimental scattering spectra could be reproduced using different distributions of realistic colloids (spheres, discs, ellipses, etc.). The results of approaches such as these must therefore be interpreted with caution, and the method used to obtain them should always be borne in mind.…”
Section: Colloidal Structure Of Aphaltenes In Solutionmentioning
confidence: 99%
“…Fairly reliable values of average volume by weight, molar mass by weight and radius of gyration can be deduced from experimental measurements without using distribution models. In contrast, Barré et al (1997) demonstrated that the experimental scattering spectra could be reproduced using different distributions of realistic colloids (spheres, discs, ellipses, etc.). The results of approaches such as these must therefore be interpreted with caution, and the method used to obtain them should always be borne in mind.…”
Section: Colloidal Structure Of Aphaltenes In Solutionmentioning
confidence: 99%
“…Concentration of copolymer in solution is 0.5% w/w (5000 ppm). Earlier SAXS studies dealing with the dispersing effect of resins [28] and the influence of temperature [27] report significant changes in asphaltene size thus proving that technique is well suited for such measurements. Consequently, we infer that the three copolymers have no effect on the size of asphaltene aggregates in toluene.…”
Section: Saxsmentioning
confidence: 99%
“…In this case, R s is related to the mass M w and to the fractal dimension D s of aggregates in the adsorbed state by: (25) where p is a prefactor. The combination of Equations (24) and (25) leads to an expression whose form is similar to (23): (26) Identification of the exponent value in relation (23) and Equation (26) lead to a numerical value of D s close to 3, which means that aggregates lose their fractal character in the adsorbed state. Asphaltene volume fractions in the adsorbed layer were estimated with the help of additional mass density data: it has been shown that the volume fraction of asphaltene changes from a few percent in volume aggregate to roughly 40 percent in the adsorbed layer.…”
Section: Adsorption Of Asphaltene Aggregates At the Solid/liquid Intementioning
confidence: 99%